Minat Siswa dalam Mengikuti Kegiatan Ekstrakulikuler Sepakbola di SMPN 2 Purwadadi - Agus Kurnia; Muhammad Mury Syafei; Tedi Purbangkara (Jurnal Ilmiah Wahana Pendidikan, 2021)
The problem of this research is that the researcher suspected the decrease of students’ interest in extracurricular football activities at SMP Negeri 2 Purwadadi in Purwadadi. This research used quantitative descriptive research as a research design and used a survey method as collecting the data. The data collection technique used a questionnaire instrument and the data were analysis by using descriptive statistics with percentages. The population of this research were student of grade VIII at SMP Negeri 2 Purwadadi. However, the research used the purposive sampling technique along with 30 students as respondents. From the results of this research, it is known that the level of student interest in participating in extracurricular football activities at SMPN 2 Purwadadi states in the "Very Good" category with a percentage of 7% with a total of 2 students, in the "Good" category with a percentage of 17% with a total of 5 students, in the category " Fairly Good" with a percentage of 47% with a total of 14 students, in the "Poor Good" category with a percentage of 10% with a total of 6 students, and in the "Very Poor" category with a percentage of 10% with a total of 3 students. The results showed that students' interest in participating in extracurricular football activities at SMPN 2 Purwadadi was at pretty good category.